Aplicación del software educativo en el proceso de enseñanza - aprendizaje de la asignatura ciencias naturales del octavo año de educación general básica del Colegio Fiscal Técnico Santa Rosa del cantón Santa Rosa en el periodo lectivo 2012-2013. - Orellana Cabrera, Julio Jaker (2014)
At school High School "Santa Rosa", was investigated on the implementation of educational software in the process of learning in students of 8th year of basic education in the subject of natural sciences, through research it was observed that some teachers do not use ICT appropriately to the teaching-learning process, thus proving that teachers should be prepared to play and update properly its educational work. This research yielded information on the importance of applying an educational program on academic development in the 8th year of basic education through processes , theories, paradigms and pedagogical models used in education they have to train students . We are in the technological age and ICT we make the set of resources required to manipulate information, and therefore are a necessary and helpful in education tool therefore contributes efficiently in the PEA, achieving an active and meaningful learning. The results of the research were able to identify the variables involved in each scenario, by analyzing each question posed in the techniques used: direct, interview, observation survey, which established the lack of implementation of educational software and therefore the low technology implementation by teachers. As mentioned I would propose a seminar / workshop teacher training on the implementation of educational software to support the teaching and learning of students in 8th year of basic education, making teachers up to date in the implementation of this tool technology, which develops student skills and abilities that enable them to meet the challenges of society.